Negotiation of the Prehistoric Past for the Creation of the Global Future: "Back to Nature" Worldview and Golden Age Myth among Lithuanian Anastasians. (16th November 2018) - Pranskevičiūtė-Amoson, Rasa
Abstract : The article presents a study into the implementation of environmental and spiritual ideas of alternative communitarian movements during the establishing of quickly spreading nature-based spirituality communities and their settlements in the East-Central European region. It focuses on the Anastasia "spiritual" movement, classifiable as New Age, which emerged in Russia in the aftermath of the collapse of the Soviet Union, and since has spread to East-Central Europe and beyond. It considers the process of indigenization via assembled nature-based spiritualities and traditionalistic ideas in the movement. It will discuss how the Anastasian process of sacralization of natural space, together with the romantic mode of a narrativization of the archaic past, serve as a source for the formation of images of "indigenousness" in the movement. During the process of "indigenization, " a negotiation, interpretation and presentation of nationalistic and traditionalistic ideas serve as a basis for an imagination of (trans)local prehistoric and local national pasts— including a golden age myth, a "back to nature" worldview with attempts to reconstruct variously perceived traditions, as well as a development of utopian visions of a prospective heaven on earth—intended to widely spread future social projects. The findings are based on data obtained from fieldwork in 2005–2015, including participant observation and interviews with respondents in the Baltic countries and Russia.